A simple BF3 Et2O-mediated cycloaddition reaction to the formation of cyclic monoterpenoid pyrano[3,2-a]carbazole alkaloids - Tan, Siow-Ping (Tanjung Malim, 2021)
A simple BF3 Et2O-mediated cycloaddition reaction to the formation of cyclic monoterpenoid pyrano[3,2-a]carbazole alkaloids by Tan, Siow-Ping